Perceptions of Student Learning Facilitation During COVID-19 Pandemic in Community Schools of Shankharapur Municipality, Nepal - Shah , Shailendra Kumar (Educational Journal, 2025)
The COVID-19 pandemic shattered the education system worldwide with a sudden transition to online and blended learning, particularly in low- and middle-income countries like Nepal. Nepal's community schools were hit hard with students, teachers, and parents adapting to Alternative Learning Facilitation (ALF) such as online learning, radio, and television learning. This study examines the perception of students, teachers, and parents regarding ALF in Shankharapur Municipality, namely on issues of slow internet connection, lack of access to devices, and technical problems. The research employed qualitative methodology with descriptive research design using primary and secondary data. Primary data were collected from students, teachers, and parents of Shankharapur Municipality, while secondary data were collected from relevant newspapers, books, and websites. Parent support was vital in the learning process of students, but parents' digital illiteracy aggravated the situation. The study centers on the need for a combined learning process, both online and offline, to improve students' engagement and performance. The study also calls for the need for teacher and parental guidance, closing the digital divide, and providing even access to educational materials. While ALF was inevitable during lockdowns, its limitations, such as a lack of interactivity and real-time evaluation, were evident. The research offers recommendations to close the digital divide, enhance teacher and parent training, and integrate hybrid models of learning to improve the overall effectiveness of ALF in future learning environments.